Pengelolaan Pembelajaran Alphabet Inggris dalam Program Pemberdayaan Masyarakat di Asean Community Center Thailand - Aeny, Farah; Nurhalim, Khomsun; Utsman, Utsman (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2018)
This study aims to describe and analyze the management of learning and knowing and supporting an inhibiting factor in the management of learning the English alphabet. The study was conducted at the Asean Community Center Kamphaeng Phet, Rattaphum, Songkhla, Thailand with qualitative descriptive approach and validity of the data with source triangulation techniques, the research subjects learners and facilitators. Data analysis techniques through a phase of data reduction, data presentation, and conclusion. The results showed the management of learning the English alphabet there are elements of Planning, Implementation, Evaluation. Source of funding activities have been provided as well as an active Participation and support from the community. Learning barriers include inadequate infrastructure, lack of varied instructional guide books, as well as the implementation of learning is not structured for the learning process goes on when the arrival of volunteers. English alphabet learning management already underway in accordance with the expected goals, but you should need any more motivation, increase the use of the method in accordance with the needs of learners.menghormati sesama temannya dan kepada fasilitator. Kata Kunci: Pengelolaan Pembelajaran; Pemberdayaan; Alphabet Inggris.